2018
DOI: 10.48550/arxiv.1805.07116
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Security Vulnerabilities Against Fingerprint Biometric System

Mahesh Joshi,
Bodhisatwa Mazumdar,
Somnath Dey

Abstract: The biometric system is an automatic identification and authentication system that uses unique biological traits, such as fingerprint, face, iris, voice, retina, etc. of an individual. Of all these systems, fingerprint biometric system is the most widely used because of its low cost, high matching speed, and relatively high matching accuracy. Due to the high efficiency of fingerprint biometric system in verifying a legitimate user, numerous government and private organizations are using this system for securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…The physiological biometrics mentioned include fingerprint, face, hand, iris, ear acoustic, vascular patterns, electrocardiogram (ECG) and deoxyribonucleic acid (DNA). However, Joshi et al [27] performed a security analysis on the fingerprint system alone and confirmed that there were 16 possible attack points. Devices such as smartphones are using biometric authentication systems, such as facial authentication (FA) techniques.…”
Section: Related Workmentioning
confidence: 98%
“…The physiological biometrics mentioned include fingerprint, face, hand, iris, ear acoustic, vascular patterns, electrocardiogram (ECG) and deoxyribonucleic acid (DNA). However, Joshi et al [27] performed a security analysis on the fingerprint system alone and confirmed that there were 16 possible attack points. Devices such as smartphones are using biometric authentication systems, such as facial authentication (FA) techniques.…”
Section: Related Workmentioning
confidence: 98%
“…All these methods have their advantages and disadvantages. The finger scanner enables costeffective, secure and personalized authentication [95,4]. A similar method is the scan of the hand geometry, in which hand vein patterns or geometric features of the hand can be captured [102,103].…”
Section: Introductionmentioning
confidence: 99%
“…All these methods have their advantages and disadvantages. The finger scanner enables costeffective, secure and personalized authentication [97,4]. A similar method is the scan of the hand geometry, in which hand vein patterns or geometric features of the hand can be captured [104,105].…”
Section: Introductionmentioning
confidence: 99%